Ajaran Etika Dan Moral Dalam Surat-Surat Paulus: Relevansinya Bagi Masyarakat Modern - Jefri Feoh; Abad Jaya Zega (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
This research discusses the teachings of ethics and morals contained within the letters of Paul in the New Testament. The main focus of this study is to explore the ethical and moral values taught by Paul within the context of his letters and their relevance to modern society. Textual and contextual analysis methods are employed to identify the moral principles emphasized by Paul in various aspects of life, including interpersonal relationships, social responsibility, and personal integrity. The research findings indicate that Paul's letters contain ethical guidelines rooted in Christian principles, such as love, humility, and forgiveness. These teachings are analyzed within the cultural and social context of their writing, and are connected to the ethical challenges faced by modern society. Despite being written thousands of years ago, the moral principles taught by Paul remain relevant in addressing contemporary ethical issues, such as business ethics, human rights, and the environment. This study provides insights into how the teachings of ethics and morals in Paul's letters can be applied and adapted within the context of modern society. The practical implications of this research are to encourage further reflection on the values inherited from Paul's teachings and how these values can shape the perspectives and actions of society in facing current moral challenges.